Propuesta para la producción de abono orgánico mediante el compostaje de los residuos sólidos del municipio el Rosal, Cundinamarca (2017)
The progressive increase of the solid waste has generated a concern in the disposal of these what leads to the application of technologies totally friendly with the environment taking advantage of the availability of this raw material and at the same time it contributes in the generation of a product of interest being one of them being composting. From this problem emerges this project in order to make a proposal for the production of organic fertilizer by composting organic solid waste of the municipality of El Rosal, Cundinamarca.